Assessment of synergistic efficacy of carbaryl in combination with Cinnamomum cassia and Origanum vulgare essential oils against Dermanyssus gallinae - Zhonghao Wang; Kai Xu; Shuo Yin; Jing Liu; Jianhua Qin; Dehe Wang; Lijun Xu; Chuanwen Wang (Poultry Science)
The poultry red mite Dermanyssus gallinae, a prevalent ectoparasite in egg-laying poultry, severely compromises bird health and impedes the poultry industry's development. However, the escalating drug resistance due to sustained reliance on chemical acaricides highlights the urgent need for new mite management strategies. Therefore, plant essential oils (EOs), which exhibit natural acaricidal properties and environmental compatibility, represent promising candidates for developing eco-friendly acaricides. In this study, we formulated binary mixtures of the median lethal concentrations (LC50) of carbaryl and EOs of Cinnamomum cassia and Origanum vulgare at ratios from 1:9 to 9:1 and then evaluated their contact toxicity, fumigant toxicity, and ovicidal effects against D. gallinae. The binary mixtures of C. cassia–carbaryl (2:8), O. vulgare–carbaryl (6:4), and C. cassia–O. vulgare (7:3) exhibited the most effective contact toxicity and achieved mite mortality rates of 60 %, 66.7 %, and 65.5 %, respectively, with poison ratios of 1.22, 1.25, and 1.24, respectively, indicating synergism. In the fumigant trials, the O. vulgare–carbaryl (6:4) mixture achieved 97 % mite mortality at 48 h, whereas the C. cassia–carbaryl (2:8) mixture demonstrated low mite mortality of 18 %. Notably, the C. cassia–O. vulgare mixture at 7:3 resulted in 87 % mite mortality, which was lower than that of the other ratios for this mixture. Furthermore, the ovicidal effects of the optimal binary mixtures of C. cassia–carbaryl (2:8), O. vulgare–carbaryl (6:4), and C. cassia–O. vulgare (7:3) were significantly better than those of a single drug, with egg hatchabilities of 2.3 %, 6.6 %, and 4.3 %, respectively, thus indicating strong inhibition of D. gallinae eggs. These combinations outperformed the single-agent controls, with egg hatchability rates of 31 % for C. cassia EO, 33.3 % for O. vulgare EO, and 20 % for carbaryl. Compared with the control group, mite eggs treated with the optimal binary mixtures and single drugs exhibited significant shrinkage and structural damage, which are consistent with low egg hatchability. These results demonstrate that integrating EOs with carbaryl could represent a viable alternative strategy for the management of poultry red mites.